EFL students’ perception on the use of Grammarly and teacher feedback - Fahmi, Mohammad Amiqul; Cahyono, Bambang Yudi (Universitas Muhammadiyah Sidoarjo, 2021)
Many studies on the Automated writing evaluation (AWE) Program predominantly focused on the outcomes of the students writing and the comparison between AWE programs. However, studies investigating the students' perception on combining an AWE program and teacher feedback are still insufficient. This study examined the students' perception on the use of Grammarly and teacher feedback on their writing. It also sought to know whether the students' English proficiency level influences their perception. The participants included 26 undergraduate students of the Faculty of Law who were taking an English for Specific Purpose (ESP) Writing course when the data were collected. The data were the students' responses to the questionnaire and their TOEFL scores. The result of the analysis showed that the students perceived the use of Grammarly and teacher feedback positively. Furthermore, the students' perception on the use of Grammarly and teacher feedback was not influenced by their English proficiency level. Students of high and low English proficiency levels gave positive responses to the use of Grammarly and teacher feedback. HIGHLIGHTS: Combining two kinds of feedback (AWE program and the teacher) providers will produce the feedback that is truly helpful for both the teacher and the students. The role of teacher feedback cannot be neglected as it can complement the demerits of the AWE program. English teachers should consider the appropriate approach when using Grammarly for students with certain English proficiency level because students from different English proficiency levels need a different approach.